Comparing Alternative Reimbursement Methods in a Model of Public Health Insurance - Lucio Picci; Miriam Golden (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
Standard crossnational measures of corruption draw on information collected through surveys. We propose a novel alternative measure based on objective data, namely, the difference between a measure of the physical quantities of public infrastructure and a measure of the value of public capital stocks. Where the difference between the value of existing infrastructure and the actual physical infrastructure is larger, more money is being siphoned off in mismanagement, fraud, bribes, kickbacks, and embezzlement; that is, corruption is greater. We create this measure for Italy's 20 regions as of the mid-1990s, controlling for possible regional differences in the costs of public construction. We analyze data over the Italian regions to demonstrate the utility of the proposed measure. The analysis shows that corruption is greater in the southern Italian regions, as would be expected. Our proposed measure exhibits a strong statistically significant relationship inverse with Putnam's measure of government performance, suggesting that as corruption increases, government performance deteriorates. Finally, we show that high-level political malfeasance measured by the number of charges of malfeasance against members of Italy's Chamber of Deputies in the period from 1992 to 1994 is highly and significantly correlated with the more general measure of corruption that we propose.
Keywords: 330